A Study On The Somalian Science Teachers Initiatives In Coping With The English Language In The Teaching And Learning Process - Diriye, Fardowsa (2013)
The topic of this study is the medium of instruction in secondary schools in Somalia. The study investigated the extent of the problem of English proficiency among teachers and the way cope with the English medium dilemma during science lessons. An important question this study was concern with the ways Somali secondary school science teacher surmount the problem of medium of instruction and what initiatives they take to cope with the linguistic barrier so as to make learning more effective and hence improve academic performance.